Electrolyte and application thereof
By introducing specific functional additives into the electrolyte, the oxidative decomposition of the electrolyte and transition metal ion dissolution caused by the structural instability of the nickel-manganate lithium material are solved, and the high-voltage and thermal stability of the battery is achieved, and the circulation and storage performance are optimized.
Patent Information
- Application Number
- CN202411997397.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Lithium nickel manganate (LiNi0.5Mn1.5O4, LNMO) materials have structural instability during production and use, resulting in oxidation and decomposition of electrolytes and dissolution of transition metal ions, affecting the cycling and storage performance of the battery.
By introducing specific functional additives into the electrolyte, including carbon-nitrogen triple bonds, conjugated structures, N elements and S elements, the high pressure and thermal stability of the electrolyte are improved, the uniformity and stability of the positive and negative electrode interface film are promoted, and the dissolution of transition metal ions is inhibited.
It effectively improves the high-voltage stability and thermal stability of the electrolyte, promotes the interface stability of the positive and negative electrodes, and optimizes the cycle performance and storage performance of the battery.
Smart Images

Figure CN119764557A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of lithium-ion batteries, and specifically relates to an electrolyte and its application. Background Art
[0002] With the vigorous development of the new energy vehicle industry, the demand for high energy density power batteries is becoming increasingly urgent. The development of high voltage cathode materials and their adaptive electrolytes has become the main research direction for the next generation of high energy density power batteries. 0.5 Mn 1.5 O4, LNMO) materials have attracted widespread attention for their high voltage (4.7V, vs. Li / Li+), high energy density (up to 650W·h / kg), high theoretical specific capacity (146.7mAh / g), abundant resources and low price. However, LNMO currently has some shortcomings that limit its application. The shortcomings are: ① In the production of lithium nickel manganese oxide, the surface is exposed to strong oxidizing Ni 4+ ② The PF5 produced by the decomposition of LiPF6 under high potential and high temperature reacts with the trace water in the electrolyte system to generate HF, which accelerates the oxidation of Mn in the LNMO structure. 2+ dissolves, thus causing structural instability, and the dissolved Mn 2+ It is reduced at the negative electrode, resulting in capacity decay during electrolyte cycling.
[0003] Ion doping, surface coating and composite methods are the methods to improve LiNi 0.5 Mn 1.5 An effective way to improve the electrochemical performance of LNMO materials. However, the above methods all involve certain synthesis methods, complex processes, and troublesome modification methods. From the perspective of electrolyte, the use of electrolyte additives is one of the most economical and effective ways to solve the above problems of LNMO. Therefore, a high-voltage electrolyte suitable for it is developed to improve the electrochemical performance of LiNi 0.5 Mn 1.5 The interfacial stability between the O4 electrode and the electrolyte is important for improving the 0.5 Mn 1.5 O4 battery performance is of great significance. Summary of the invention
[0004] In order to solve the problems and deficiencies in the prior art, the present application provides an electrolyte and its application. The electrolyte can improve the oxidation resistance of the electrolyte under high voltage by introducing specific functional additives, and can form a uniform and dense CEI film at the positive electrode, inhibit the dissolution of transition metal ions, and further promote the stability of the negative electrode SEI film. Therefore, the electrolyte provided in the present application can further promote the interface stability of the positive and negative electrodes, thereby optimizing the electrochemical properties of the battery such as the cycle performance.
[0005] According to the first aspect of the present application, an electrolyte is provided, comprising a lithium salt, an organic solvent, and a functional additive; the structural formula of the functional additive is as follows:
[0006]
[0007] This application can effectively improve the overall high-voltage stability of the electrolyte by introducing the functional additive of the above structure, so that the electrolyte is not easily oxidized under high pressure and still maintains good stability. At the same time, after the introduction of the functional additive, the electrolyte can promote the uniformity and stability of the positive electrode interface CEI and the negative electrode interface SEI film, thereby reducing the interface side reactions, while reducing the dissolution of transition metals, reducing the damage of transition metal ions to the negative electrode SEI film, and effectively improving the room temperature and high temperature cycle performance and storage performance of the high-voltage battery system.
[0008] Specifically, among the above functional additives, firstly, the carbon-nitrogen triple bond can, to a certain extent, eliminate or alleviate the adverse effects of water and hydrofluoric acid in the electrolyte, and reduce the harm caused by them; for example, the nitrogen atom in the carbon-nitrogen triple bond has a certain electronegativity, and there are lone pairs of electrons on it, which can form hydrogen bonds with water molecules, restricting the free movement and reactivity of water, and the presence of the carbon-nitrogen triple bond will make the molecules connected to it have a certain electron delocalization effect. This change in electron distribution can affect the polarity and chemical properties of the molecule. When the additive containing the carbon-nitrogen triple bond interacts with water, it will cause a certain change in the electron cloud distribution of water, thereby reducing the chemical reactivity of water and reducing the possibility of side reactions between water and other components in the electrolyte. Similarly, the nitrogen atom in the carbon-nitrogen triple bond can act as an electron pair donor, and react with the hydrogen ions in hydrofluoric acid to form a relatively stable complex. This complexation can reduce the effective concentration of hydrofluoric acid, thereby reducing its corrosiveness to electrodes and electrolytes.
[0009] Secondly, the trinitrogen pentacyclic ring, carbonyl group, benzene ring, and nitrogen-sulfur pentacyclic ring can together form a large conjugated structure, which is beneficial to improve the molecular antioxidant and thermal stability, making it difficult to decompose or react under high temperature and high pressure, slowing down the oxidative decomposition of the electrolyte, extending the service life of the electrolyte, and reducing the impurities generated by thermal decomposition, thereby improving the thermal stability of the electrolyte. Moreover, the conjugated system can interact with the electrode surface to promote the stability of the negative electrode SEI film, and can also combine with the active sites on the electrode surface through π-π interaction, hydrogen bonds, etc., to reduce the interfacial tension between the electrode and the electrolyte, so that the electrolyte can better infiltrate the electrode, thereby improving the battery's charge and discharge efficiency and power performance, and then optimizing the battery's normal temperature, high temperature cycle performance and storage performance. In addition, this large conjugated system can form a structure similar to a "molecular wire" in the electrolyte (ions can migrate along the π electron cloud of the conjugated system), providing a channel for the transmission of metal ions such as lithium ions, and improving the lithium ion transmission rate.
[0010] Third, the N element in the functional additive can coordinate with the transition metal ions, reduce the damage of the transition metal ions in the electrolyte to the negative electrode SEI film, and further improve the stability of the negative electrode SEI film during the charge and discharge cycle.
[0011] Fourthly, the S element in the functional additives can form CEI and SEI films containing sulfides with better lithium conductivity, thereby further improving the rate performance of the battery.
[0012] Therefore, the introduction of the functional additives with the above-mentioned specific structure can further promote the stability of the positive and negative electrode interfaces, while making the electrolyte have higher high voltage and thermal stability, thereby further optimizing the battery's room temperature, high temperature cycle performance and storage performance.
[0013] Preferably, in the functional additive, R1 includes at least one of hydrogen, alkyl chain, substituted alkyl chain, alkyl chain with branch, substituted alkyl chain with branch, and halogen; R2 includes at least one of hydrogen, alkyl chain, substituted alkyl chain, alkyl chain with branch, substituted alkyl chain with branch, and halogen; R3 includes at least one of alkyl chain, substituted alkyl chain, alkyl chain with branch, and substituted alkyl chain with branch.
[0014] Preferably, in the functional additive, R1 comprises hydrogen; R2 comprises hydrogen; and R3 comprises an alkyl chain.
[0015] Preferably, in the functional additive, R1 includes hydrogen; R2 includes hydrogen; and R3 includes -CH2-.
[0016] Preferably, the structural formula of the functional additive is as follows:
[0017] Its CAS number is 202416-78-2.
[0018] Preferably, the mass proportion of the functional additive in the electrolyte is 0.3-1.0wt%. Controlling the mass proportion of the functional additive in the electrolyte within the above range can ensure that there are enough functional additives to improve the overall performance of the electrolyte and the battery, and can ensure that there are no excessive functional additives that affect the functions of other components in the electrolyte, or affect the solubility of the functional additives and other electrolyte components in the solvent, etc., resulting in a decrease in the overall performance of the electrolyte, and the performance of the battery cannot be fully improved.
[0019] Preferably, the electrolyte further comprises a sulfur-containing additive; the sulfur-containing additive comprises at least one of vinyl sulfite (ES), methylene disulfonate (MMDS) and vinyl sulfate (DTD). Furthermore, the addition of the sulfur-containing additive, in conjunction with the above-mentioned functional additive, can not only further improve the high voltage resistance and heat resistance of the electrolyte, but also will not affect the role of other components of the electrolyte, thereby further improving the overall performance of the electrolyte, and further improving the normal temperature, high temperature cycle performance and storage performance of the battery.
[0020] Preferably, the mass proportion of the sulfur-containing additive in the electrolyte is 0.5-2 wt %.
[0021] Preferably, the sulfur-containing additive includes vinyl sulfite and methylene disulfonate; the mass ratio of vinyl sulfite to methylene disulfonate is 2 to 5: 1. When the sulfur-containing additive includes the above two substances, and the mass ratio of the two substances is limited to a specific range, the electrolyte obtained by the sulfur-containing additive and the above specific functional additive has better overall performance, and further promotes the stability of the positive and negative electrodes of the battery, thereby further optimizing the normal temperature and high temperature cycle performance and storage performance of the battery.
[0022] Preferably, the electrolyte further comprises carbonate additives; carbonate additives include at least one of vinylene carbonate (VEC) and fluoroethylene carbonate (FEC). Furthermore, the electrolyte in the present application also contains carbonate additives, which can form a film on the negative electrode and optimize the interface stability of the negative electrode of the battery, but too little addition will not form a dense SEI film, and too much addition will lead to high impedance and high-temperature gas production.
[0023] Preferably, the carbonate additive accounts for 0.2-1 wt % by weight in the electrolyte.
[0024] Preferably, the carbonate-based additive includes vinylene carbonate (VEC).
[0025] Preferably, the electrolyte further comprises a lithium salt additive, and the lithium salt additive comprises at least one of lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(oxalatoborate) (LiBOB), lithium difluorophosphate (LiPO2F2), and lithium difluorobis(oxalatoborate) (LiODFB). Furthermore, further, for the above-mentioned specific functional additives, sulfur-containing additives, and carbonate additives, the present application further adds lithium salt additives to further promote the overall conductivity and lithium ion transmission efficiency of the electrolyte, so that it and the above-mentioned additives work together to show better resistance to high pressure and heat stability, and ultimately the performance of the battery is further optimized.
[0026] Preferably, the mass proportion of the lithium salt additive in the electrolyte is 0.5-1.0 wt%.
[0027] Preferably, the lithium salt additive comprises lithium difluorophosphate.
[0028] Preferably, the lithium salt additive includes lithium difluorophosphate and lithium bis(oxalatoborate). The selection of these two lithium salt additives is more conducive to the overall performance of the electrolyte, and thus more conducive to further optimization of battery performance. Preferably, the mass ratio of lithium difluorophosphate to lithium bis(oxalatoborate) is 3 to 6:1.
[0029] Preferably, the lithium salt includes lithium hexafluorophosphate; and the concentration of lithium hexafluorophosphate in the electrolyte is 1 to 1.5 mol / L.
[0030] Preferably, the organic solvent includes at least one of ethylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.
[0031] Preferably, the organic solvent includes at least two or at least three of ethylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.
[0032] Preferably, the volume ratio of ethylene carbonate, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate is (20-40):(0-20):(0-20):(30-50).
[0033] According to a second aspect of the present application, a battery is provided, characterized in that it includes the above-mentioned electrolyte.
[0034] Preferably, the battery includes a nickel-manganese-oxide lithium cathode material. In particular, the electrolyte provided in the present application is targeted at batteries with a high-voltage system such as a nickel-manganese-oxide lithium cathode material system, and exhibits greater adaptability, that is, the battery has better cycle performance and storage performance under high voltage and high temperature. DETAILED DESCRIPTION
[0035] In order to enable those skilled in the art to better understand the present application, the technical solutions in the embodiments of the present application will be clearly and completely described below. Obviously, the described embodiments are only embodiments of a part of the present application, rather than all of the embodiments.
[0036] Example 1
[0037] 1. Electrolyte composition and preparation
[0038] The electrolyte in this embodiment includes lithium salt, organic solvent, functional additive, sulfur-containing additive, carbonate additive, and lithium salt additive.
[0039] The lithium salt is lithium hexafluorophosphate (LiPF6), and the concentration of lithium hexafluorophosphate in the electrolyte is 1 mol / L.
[0040] The organic solvent consists of ethylene carbonate, diethyl carbonate and ethyl methyl carbonate. Taking the total volume of the organic solvent as 100%, the volume fraction of ethylene carbonate is 30%, the volume fraction of diethyl carbonate is 20% and the volume fraction of ethyl methyl carbonate is 50%.
[0041] Functional additives are The mass percentage in the electrolyte is 0.3wt%.
[0042] The sulfur-containing additive is methylene methanedisulfonate (MMDS), and its mass proportion in the electrolyte is 1wt%.
[0043] The carbonate additive is vinyl ethylene carbonate (VEC), and its mass proportion in the electrolyte is 0.3 wt %.
[0044] The lithium salt additive is lithium difluorophosphate (LiPO2F2), which accounts for 0.5wt% of the electrolyte.
[0045] The preparation of the electrolyte follows the following steps: in an argon atmosphere, adding a formulated amount of carbonate additive, lithium salt additive, sulfur-containing additive and functional additive to an organic solvent, then adding lithium salt, stirring and mixing at a temperature of 10° C. to obtain an electrolyte.
[0046] 2. Preparation of batteries
[0047] Preparation of lithium-ion batteries
[0048] (1) Preparation of positive electrode
[0049] The ternary material LNMO (LiNi 0.5 Mn 1.5O4) positive electrode active material, binder PVDF (polyvinylidene fluoride), conductive agent SP (conductive carbon black Super-P) are mixed and stirred in a mass ratio of 94:3:3 to obtain positive electrode slurry, and then the positive electrode slurry is coated on aluminum foil through a coating process, and a positive electrode sheet is obtained after vacuum drying and cold pressing processes.
[0050] (2) Preparation of negative electrode sheet
[0051] The negative electrode material graphite, conductive agent SP (conductive carbon black Super-P), binder CMC (carboxymethyl cellulose) and SBR (styrene-butadiene rubber) are mixed and stirred evenly in a mass ratio of 94:1:2:3 to obtain a negative electrode slurry, and then the negative electrode slurry is coated on a copper foil through a coating process, and a negative electrode sheet is obtained after vacuum drying and cold pressing processes.
[0052] (3) Selection of electrolyte
[0053] The electrolyte prepared in this example is used.
[0054] (4) Selection of isolation membrane
[0055] Celgard 2400 was selected as the separator for lithium-ion batteries.
[0056] (5) Preparation of lithium-ion batteries
[0057] The positive electrode sheet, isolation film (Celgard2400), and negative electrode sheet are stacked in order, so that the isolation film is between the positive electrode sheet and the negative electrode sheet to play an isolating role. The bare battery cell is placed in an outer packaging shell, and the electrolyte is injected after drying. After vacuum packaging, standing, forming, shaping and other processes, a soft-pack lithium-ion battery is obtained.
[0058] Example 2
[0059] The difference between this embodiment and embodiment 1 is that, in the prepared electrolyte, the mass proportion of the functional additive in the electrolyte is adjusted to 0.15%; the rest is consistent with embodiment 1.
[0060] Example 3
[0061] The difference between this embodiment and embodiment 1 is that, in the prepared electrolyte, the mass proportion of the functional additive in the electrolyte is adjusted to 1.5%; the rest is consistent with embodiment 1.
[0062] Example 4
[0063] The difference between this embodiment and embodiment 1 is that, in the prepared electrolyte, the mass proportion of the functional additive in the electrolyte is adjusted to 0.6%; the rest is consistent with embodiment 1.
[0064] Example 5
[0065] The difference between this embodiment and embodiment 1 is that in the prepared electrolyte, the sulfur-containing additive is adjusted to vinyl sulfite and methylene disulfonate, and the mass ratio of the two is 3.5:1, and the total amount of the sulfur-containing additive added remains unchanged; the rest is consistent with embodiment 1.
[0066] Example 6
[0067] The difference between this embodiment and embodiment 1 is that in the prepared electrolyte, the sulfur-containing additive is adjusted to vinyl sulfite and methylene disulfonate, and the mass ratio of the two is 7:1, and the total amount of the sulfur-containing additive added remains unchanged; the rest is consistent with embodiment 1.
[0068] Example 7
[0069] The difference between this embodiment and embodiment 1 is that in the prepared electrolyte, the sulfur-containing additive is adjusted to diethyl sulfate (DTD); the rest is the same as embodiment 1.
[0070] Example 8
[0071] The difference between this embodiment and embodiment 1 is that in the prepared electrolyte, the carbonate additive is adjusted to fluoroethylene carbonate (FEC); the rest is the same as embodiment 1.
[0072] Example 9
[0073] The difference between this embodiment and embodiment 1 is that in the prepared electrolyte, the carbonate additive is adjusted to vinylene carbonate (VEC) and fluoroethylene carbonate (FEC), and the mass ratio of the two is 1:1, and the total amount of carbonate additive added remains unchanged; the rest is consistent with embodiment 1.
[0074] Example 10
[0075] The difference between this embodiment and embodiment 1 is that in the prepared electrolyte, the lithium salt additive is adjusted to lithium difluorophosphate and lithium bis(oxalatoborate), and the mass ratio of the two is 4.5:1, and the total amount of the lithium salt additive added remains unchanged; the rest is consistent with embodiment 1.
[0076] Embodiment 11
[0077] The difference between this embodiment and embodiment 1 is that in the prepared electrolyte, the lithium salt additive is adjusted to lithium bis(fluorosulfonyl)imide and lithium bis(oxalatoborate), and the mass ratio of the two is 4.5:1, and the total amount of the lithium salt additive added remains unchanged; the rest is consistent with embodiment 1.
[0078] Comparative Example 1
[0079] The difference between this comparative example and Example 1 is that no functional additive is added to the prepared electrolyte; the rest is the same as Example 1.
[0080] Comparative Example 2
[0081] The difference between this comparative example and Example 1 is that in the prepared electrolyte, the functional additive is adjusted to The CAS number is 202416-80-6; the rest is consistent with Example 1.
[0082] Comparative Example 3
[0083] The difference between this comparative example and Example 1 is that in the prepared electrolyte, the functional additive is adjusted to The CAS number is 35272-37-8; the rest is consistent with Example 1.
[0084] Comparative Example 4
[0085] The difference between this comparative example and Example 1 is that in the prepared electrolyte, the functional additive is adjusted to The CAS number is 175473-30-0; the rest is consistent with Example 1.
[0086] Comparative Example 5
[0087] The difference between this comparative example and Example 1 is that in the prepared electrolyte, the functional additive is adjusted to The CAS number is 139540-11-7; the rest is consistent with Example 1.
[0088] Test Case
[0089] 1. Experimental Construction Method
[0090] The HF content of the electrolytes prepared in all the above embodiments and comparative examples was measured, and the cycle performance and high-temperature storage performance of the batteries prepared in all the above embodiments and comparative examples were tested. The specific testing methods are as follows.
[0091] (1) HF content determination
[0092] The electrolyte was stored at 45°C, and the HF contents at 0d and 15d were measured by ice water titration, respectively, and recorded as HF-0d and HF-15d.
[0093] (2) Cyclic performance test
[0094] Normal temperature (25°C) cycle test: Place the battery at 25°C, record the initial capacity as A1, and the capacity after 1C / 1C cycle to 1000 cycles as A2. Calculate the capacity retention rate of the battery after 1000 cycles of high temperature cycle by the following formula: Cycle capacity retention rate (%) = A2 / A1×100%.
[0095] High temperature (45°C) cycle test: Place the battery at 45°C, record the initial capacity as A1, and the capacity after 1C / 1C cycle to 1000 cycles as A2. Calculate the capacity retention rate of the battery after 1000 cycles of high temperature cycle by the following formula: Cycle capacity retention rate (%) = A2 / A1×100%.
[0096] The above 1C / 1C cycle means that the battery is charged at a constant current of 1.0C (nominal capacity) to a voltage of 4.4V, then charged at a constant voltage of 4.4V to a current ≤0.05C, and after standing for 10 minutes, discharged at a constant current of 1C to 2.8V. The above is one charge and discharge cycle.
[0097] (3) High temperature storage performance test
[0098] The battery was tested for 5 charge and discharge cycles at room temperature with a charge and discharge rate of 1C, and then charged to a fully charged state at a rate of 1C. The 1C capacity Q0 and battery volume V0 were recorded respectively. The fully charged battery was stored at 60°C for 90 days, and the battery volume V1 and 1C discharge capacity Q1 were recorded. The battery was then charged and discharged at a rate of 1C for 5 weeks at room temperature, and the 1C discharge capacity Q2 was recorded. The experimental data such as the battery's high-temperature storage capacity retention rate, capacity recovery rate, and volume change rate were calculated, and the recorded results are shown in the following table. The calculation formulas used are as follows: Capacity retention rate (%) = Q1 / Q0×100%; Capacity recovery rate (%) = Q2 / Q0×100%; Volume change rate (%) = (V1-V0) / V0×100%.
[0099] The above-mentioned charge-discharge cycle at a charge-discharge rate of 1C or the charge-discharge rate of 1C means that
[0100] 1.0C (nominal capacity) constant current charge to the voltage of 4.4V, then 4.4V constant voltage charge to the current ≤ 0.05C, after leaving for 10 minutes, 1C constant current discharge to 2.8V, the above is one charge and discharge cycle or one charge and discharge.
[0101] 2. Experimental results
[0102] The relevant performance test results of the electrolytes and batteries prepared in all the above embodiments and comparative examples are shown in Table 1.
[0103] Table 1. Test results of relevant performances of electrolytes and batteries prepared in the examples and comparative examples
[0104]
[0105] As shown in Table 1, the electrolyte provided by the present invention can effectively reduce the HF content, and at the same time, the battery has better cycle performance at room temperature and high temperature, and the battery has better storage performance at high temperature. Please refer to Examples 1 to 11 for details.
[0106] In the electrolyte of Comparative Example 1, there is no functional additive, in the functional additive of Comparative Example 2, there is no cyano group, in the functional additive of Comparative Example 3, there is no cyano group and trinitrogen pentacyclic ring, in the functional additive of Comparative Example 4, there is no benzene ring and sulfur-nitrogen pentacyclic ring, and in the functional additive of Comparative Example 5, there is no sulfur-nitrogen pentacyclic ring and cyano group; all of the above factors cause the increase of HF content in the electrolyte, and the decrease of the normal temperature and high temperature cycle capacity retention rate and high temperature storage performance of the battery. In particular, in Comparative Example 1, no functional additive is added, and the HF content in the electrolyte increases more significantly, and at the same time, the various performances of the battery also decrease most significantly, which shows that the specific functional additive introduced by the present invention has a significant improvement in the performance of the electrolyte, and thus can effectively improve the various performances of the battery. In addition, it also shows that the structure of the specific functional additive introduced by the present invention has changed, especially some functional groups have changed, which has a greater impact on the performance of the functional additive and the electrolyte, and ultimately leads to a more obvious decline in the performance of the battery in various aspects.
[0107] Further comparing Example 1 with Examples 2 to 4, the content of the functional additive in the electrolyte in Examples 2 and 3 is too low and too high, respectively, which results in a decrease in the normal temperature and high temperature cycle capacity retention rate and high temperature storage performance of the battery compared to Example 1 and Example 4. This indicates that controlling the content of the functional additive in the electrolyte within a specific range is more conducive to exerting the overall performance of the electrolyte, thereby further optimizing the performance of the battery.
[0108] Comparing Example 1 with Examples 5 to 7, the sulfur-containing additive in Example 5 is vinyl sulfite and methylene disulfonate, and the mass ratio is in the range of 2 to 5:1; the sulfur-containing additive in Example 6 is vinyl sulfite and methylene disulfonate, but the mass ratio is in the range of 2 to 5:1; the sulfur-containing additive in Example 7 is vinyl sulfate; and the performance of the battery in Example 5 is slightly better than that in Example 1, and the performance of the batteries in Examples 6 and 7 is slightly worse than that in Example 1. This shows that the type selection and ratio of sulfur-containing additives have a certain influence on the performance of the electrolyte, and the selection of appropriate sulfur-containing additives and ratios is more conducive to further optimizing the performance of the electrolyte and the battery.
[0109] Comparing Example 1 with Examples 8 to 11, the carbonate additive in Example 8 is fluoroethylene carbonate (FEC), the carbonate additive in Example 9 is vinylene carbonate (VEC) and fluoroethylene carbonate (FEC), the lithium salt additive in Example 10 is lithium difluorophosphate and lithium bis(oxalatoborate), and the lithium salt additive in Example 11 is lithium bis(fluorosulfonyl)imide and lithium bis(oxalatoborate); the above factors cause the performance of the batteries in Examples 8 to 11 to be slightly worse than that in Example 1 or better than that in Example 1, which shows that the selection of suitable carbonate additives and lithium salt additives is more conducive to the overall performance of the electrolyte, and thus more conducive to further optimizing the relevant performance of the battery.
[0110] The above embodiments are only used to illustrate the technical solution of the present application rather than to limit the protection scope of the present application. Although the present application is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solution of the present application can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present application.
Claims
1. An electrolyte, characterized in that: Including lithium salts, organic solvents, and functional additives; The structural formula of the functional additive is as follows:
2. The electrolyte according to claim 1, characterized in that: In the functional additive, R1 includes at least one of hydrogen, an alkyl chain, a substituted alkyl chain, a branched alkyl chain, a branched substituted alkyl chain, and a halogen; R2 includes at least one of hydrogen, an alkyl chain, a substituted alkyl chain, a branched alkyl chain, a branched substituted alkyl chain, and a halogen; R3 includes at least one of an alkyl chain, a substituted alkyl chain, a branched alkyl chain, and a branched substituted alkyl chain.
3. The electrolyte according to claim 1, characterized in that: In the functional additive, R1 includes hydrogen; R2 includes hydrogen; and R3 includes an alkyl chain.
4. The electrolyte according to claim 1, characterized in that The structural formula of the functional additive is as follows:
5. The electrolyte according to claim 4, characterized in that The functional additive accounts for 0.3-1.0 wt % in the electrolyte.
6. The electrolyte according to claim 1, characterized in that: Also included is a sulfur-containing additive; the sulfur-containing additive includes at least one of vinyl sulfite, methylene disulfonate and vinyl sulfate; The sulfur-containing additive accounts for 0.5-2 wt % by mass in the electrolyte.
7. The electrolyte according to claim 6, characterized in that: The sulfur-containing additive includes the vinyl sulfite and the methylene disulfonate; The mass ratio of the vinyl sulfite to the methylene disulfonate is 2 to 5:
1.
8. The electrolyte according to claim 1, characterized in that: Also includes carbonate additives; the carbonate additives include at least one of vinylene carbonate and fluoroethylene carbonate; The mass percentage of the carbonate additive in the electrolyte is 0.2-1 wt %.
9. The electrolyte according to claim 1, characterized in that: Also included is a lithium salt additive, wherein the lithium salt additive includes at least one of lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), lithium difluorophosphate, and lithium difluorobis(oxalatoborate); The lithium salt additive accounts for 0.5-1.0 wt % in the electrolyte.
10. A battery, characterized in that: Comprising the electrolyte as claimed in any one of claims 1 to 9.
Citation Information
Patent Citations
Electrolyte and lithium metal battery
CN118738556A
Electrolyte and battery
CN118943489A
Negative electrode for lithium battery and lithium battery comprising same
US20040058232A1
Non-aqueous redox flow batteries
US20190319290A1
Non-Aqueous Fluorinated Electrolytes for Lithium Batteries
US20240396089A1